Bioresponsive Injectable Hydrogels for On-demand Drug Release and Tissue Engineering - Vashist, Arti (Curr Pharm Des, 2017)
The emergence of injectable hydrogels as biomaterials has been a revolutionary breakthrough in the field of on-demand drug delivery and tissue engineering. The promising features of these systems include their biodegradability, biocompatibility, permeability, ease of the surgical implantation, and most importantly exhibit minimally invasiveness. These hydrogels have been explored as sustained and on-demand release carriers for the various bioactive agents, growth factors, live cells, various hydrophobic drugs and as extracellular matrices for tissue engineering. Present review is an attempt to highlight the recent systems explored for on demand drug release and tissue engineering. It also gives an overview of the role of nanotechnology in the advancements of injectable hydrogels. The future prospects and challenges of these hydrogels have also been addressed.